TREM-1 modulation produces positive outcome on the histopathology and cytokines release profile of Plasmodium berghei-infected mice - Chin V.K.; Asyran A.M.Y.; Zakaria Z.A.; Abdullah W.O.; Chong P.P.; Nordin N.; Ibraheem Z.O.; Majid R.A.; Basir R. (Springer, 2024)
Indexed by SCOPUS